A new green method for the preparation of titanium dioxide‐graphene composite using cyclodextrin as a linker with enhanced photoexcited electron transfer and photocatalytic properties. Issue 5 (26th February 2016) - Mohamed, Mukthar Ali; Shukla, Anurudha; Sandhya, K. Y.
Abstract : In this article, we report a titanium dioxide‐graphene (TiO2 ‐CD‐GN) composite from TiO2 and reduced graphene oxide (rGO) using a new green method. TiO2 nanoparticles are anchored onto graphene nanosheets (GNs) through β‐cyclodextrin (CD) molecules using sun light irradiation. In this method, graphene is directly incorporated as rGO rather than GO into the composite. The prepared TiO2 ‐CD‐GNs exhibits reduced charge recombination compared to that of the bare TiO2, indicating effective charge separation. The composite with 0.5% of rGO (TiO2 ‐CD‐GNs0.5) shows ∼3 times higher activity to that of the bare TiO2 for the photodegradation of methylene blue. The TiO2 ‐CD‐GNs0.5 displays enhanced electron transfer. In the visible light photodegradation of 4‐chlorophenol, TiO2 ‐CD‐GNs1 exhibits the highest photocatalytic activity compared to that of the composites and bare TiO2 . Catalytic activity of the reused catalyst remains the same (62% of the initial value) from the second cycle to the next 7 cycles studied. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 1283–1292, 2016